Focusing on six action areas - Abd Razak, Dzulkifli (2009)
THE 17th Conference of Commonwealth Education Ministers (17CCEM) in Kuala Lumpur will be the biggest ever meeting of its kind since the first conference was held in Oxford 50 years ago. Malaysia is honoured to host the 50th anniversary of the conference, starting tomorrow. The fourday conference is jointly organised by the Ministry of Education and the Ministry of Higher Education, Malaysia, and the Commonwealth Secretariat. Other organising partners include the Commonwealth Foundation, the Commonwealth of Learning, the Association of Commonwealth Universities, the Commonwealth Teachers Group, and Nexus Strategic Partnerships Ltd.